Implementation of Islamic Religious Education Learning Evaluation in Developing Students' Spirituality - Nurajijah; N Ropatul Munawaroh; Melati Novalita Putri; Adi Rosadi (STIT Attaqwa, 2025)
This study focuses on the implementation of Islamic Religious Education assessment by teachers in fostering students’ spirituality at MTs Al-Atiqiyah. The issue arises from the tendency to emphasize cognitive aspects while neglecting systematic evaluation of affective and spiritual dimensions. The aim of this research is to describe how assessment is implemented to shape students’ religious character, identify supporting and inhibiting factors, and observe the impact of such assessment on students’ spiritual development. This study employed a qualitative approach with a case study method, involving two Islamic education teachers and two students as the main subjects. Data were collected through interviews, participatory observations, and documentation. The results show that spiritual assessment is conducted through daily worship routines, attitude monitoring, and supervision of religious activities. Supporting factors include the school’s religious environment and teacher engagement, while obstacles involve time constraints and limited resources. The conclusion indicates that consistent and contextual spiritual assessment contributes significantly to the development of students’ religious character. The implication is that teachers need continuous training to design holistic and value-integrated assessment strategies aligned with Islamic principles.